The relationships between malocclusion, fixed orthodontic appliances and periodontal disease. A review of the literature - van Gastel Jan; Quirynen Marc; Teughels Wim; Carels Carine (Australasian Orthodontic Journal, 2023)
To review the literature on the periodontal implications of malocclusion and fixed orthodontic appliances.